Loving-kindness moderates the association between neuroticism and anxiety symptoms among Thai older adults - Phyu, Moe P.; DeMaranville, Justin; Lerttrakarnnon, Peerasak; Wedding, Danny; Wongpakaran, Nahathai; Wongpakaran, Tinakon (Narra Sains Indonesia, 2026)
The global population is experiencing rapid aging, and the mental health needs of older adults have become an urgent public health concern, with anxiety levels becoming increasingly prevalent among older adults. In Thailand, stress and anxiety among older adults are anticipated to double in the next decade. Neuroticism, characterized by emotional instability and an impulse for negative feelings, is a significant psychological characteristic associated with anxiety. Older adults with higher neuroticism have heightened sensitivity to stress and frequently struggle with emotional regulation, hence increasing their vulnerability to anxiety and other mental health disorders. Loving-kindness, a core Buddhist principle, has been shown to benefit mental health by reducing stress, anxiety, and depression, primarily in Western or short-term settings. However, there is limited research assessing its role among older adults in Buddhist cultural contexts, such as Thailand. This study investigated whether loving-kindness moderated the relationship between neuroticism and anxiety symptoms among 232 Thai adults aged 60 and above, using secondary data collected between December 2019 and September 2022. Measures included the Neuroticism Inventory, Core Symptom Index for anxiety, and the Inner Strength-Based Inventory for loving-kindness. Multiple regression analysis evaluated potential moderating effects. The results revealed that anxiety had a positive correlation with neuroticism and a negative correlation with loving-kindness and education; nevertheless, an unexpected pattern occurred in the moderation analysis. Loving-kindness specifically enhanced the correlation between neuroticism and anxiety at high levels, rather than mitigating it. Older adults exhibiting higher levels of neuroticism and loving-kindness reported increased anxiety symptoms. Education was identified as a protective factor, exhibiting a negative correlation with anxiety. Loving-kindness did not mitigate the effect of high neuroticism on anxiety in Thai older adults. Rather, it intensified this correlation, indicating that robust prosocial characteristics lacking sufficient emotional regulation may exacerbate stressful emotions. These findings contradict prevailing theories regarding the universal advantages of loving-kindness and underscore the necessity for therapies that incorporate loving-kindness with emotional regulation and self-care in older adults.